COMPUTER PROGRAM FOR TIME SERIES REDUCTION AND ANALYSIS - Halevin, A. V. (Одеські астрономічні публікації, 2017)
The program package is elaborated which allows to view the whole data set and its parts, to scale, edit and partially reduce. The external programs are connected which allow to compute "running parabolae" fit (Andronov, 1990) and determine the individual extrema. Contrary to majority of similar programs, all determined characteristics are followed by corresponding accuracy estimates. The program is much more faster than the existing more complicated graphic editors.